SURVIVAL ANALYSIS APPLIED TO MEMBER TIME OF RETENTION TO THE HEALTH INSURANCE PROVIDER - LIMA, Caroline da Silva; SANTOS JUNIOR, Luiz Carlos; SÁ, Marcelo Coelho de (Brazilian Journal of Biometrics, 2021)
Despite the profits earned in the supplementary health segment, the number of policyholders linked to it fluctuated between 2015 and 2018, in contrast to the behavior presented between 2000 and 2014, when it only grew. In order to understand part of this flow, that is, the departure of policyholders from this market, the objective is to analyze member time of retention to the health insurance provider, based on data composed of 122,381 policyholders (and former policyholders) monitored between the years 1984 and 2018. Using the traditional survival analysis, the Kaplan-Meier estimator and parametric and semi-parametric models, the following results stand out: a) the median time of retention in the plan is 4.62 years; b) the mass of insurance provider is composed (over the years observed) predominantly of women, single, young, holders and adherents to the individual / family contract; c) according to the selected Cox model, being a man (in relation to the woman), being young (in relation to the adult), being dependent (in relation to the holder) and being married (in relation to the partner) increase the risk of leaving company analyzed. These results are expected to assist this one in (re)directing its commercial and underwriting policies.